Intronic deletions that disrupt mRNA splicing of the tva receptor gene result in decreased susceptibility to infection by avian sarcoma and leukosis virus subgroup A - Reinišová, Markéta; Plachý, Jiří; Trejbalová, Kateřina; Šenigl, Filip; Kučerová, Dana; Geryk, Josef; Svoboda, Jan; Hejnar, Jiří (Journal of virology, 2012)
The group of closely related avian sarcoma and leukosis viruses (ASLVs) evolved from a common ancestor into multiple subgroups, A to J, with differential host range among galliform species and chicken lines. These subgroups differ in variable parts of their envelope glycoproteins, the major determinants of virus interaction with specific receptor molecules. Three genetic loci, tva, tvb, and tvc, code for single membrane-spanning receptors from diverse protein families that confer susceptibility to the ASLV subgroups. The host range expansion of the ancestral virus might have been driven by gradual evolution of resistance in host cells, and the resistance alleles in all three receptor loci have been identified. Here, we characterized two alleles of the tva receptor gene with similar intronic deletions comprising the deduced branch-point signal within the first intron and leading to inefficient splicing of tva mRNA. As a result, we observed decreased susceptibility to subgroup A ASLV in vitro and in vivo. These alleles were independently found in a close-bred line of domestic chicken and Indian red jungle fowl (Gallus gallus murghi), suggesting that their prevalence might be much wider in outbred chicken breeds. We identified defective splicing to be a mechanism of resistance to ASLV and conclude that such a type of mutation could play an important role in virus-host coevolution.
Keywords: kur domácí; Poultry Diseases; Sequence Deletion; sestřih RNA; sekvence nukleotidů; Receptors, Virus; sekvenční delece; RNA Splicing; Genetic Predisposition to Disease; ptačí proteiny; Chickens; Sarcoma, Avian; molekulární sekvence - údaje; Amino Acid Sequence; Avian Proteins; virové receptory; Introns; nemoci drůbeže; introny; Animals; zvířata; sekvence aminokyselin; Alpharetrovirus; ptačí sarkom; Molecular Sequence Data; Base Sequence; genetická predispozice k nemoci